Exploring language attitudes and ideologies in university students' discussion of Irish in a context of increasing language diversity. (2nd April 2016) - Atkinson, David; Kelly-Holmes, Helen
ABSTRACT: The apparent gap between positive attitudes and low levels of everyday usage of the language is often cited as one of the greatest challenges facing Irish language revitalisation. In a context of increasing linguistic and cultural diversity in the Republic of Ireland, this article reports on a research project which set out to explore the attitudes of groups of Irish undergraduate students towards the languages which they come into contact with in their daily lives, in particular, the Irish language, using a focus group method. Four themes in particular emerge in the students' discussion of Irish as they encounter it in their everyday lives: 'functionality', 'a hidden agenda', 'exclusivity', and 'heightened culture'. The metapragmatic comments of the respondents indicate deep ambivalence towards use of the Irish language, as well as complex language-ideological positions. The linguistic authority [Woolard, 2008. Language and identity choice in Catalonia: The interplay of contrasting ideologies of linguistic authority. In K. Süselbeck, U. Mühlschlegel, & P. Masson (Eds.), Lengua, nación e identidad. La regulación del plurilingüismo en España y América Latina (pp. 303–323). Frankfurt am Main: Vervuert/Iberoamericana] of Irish as both an anonymous and authentic variety is contrasted negatively with that of allochthonous languages in Ireland, such as Polish. Our study suggests that a fuller understanding of this apparent paradox may be facilitated by qualitative approaches, which explore attitudes in depth.